2010
DOI: 10.1177/105382590903200303
|View full text |Cite|
|
Sign up to set email alerts
|

Contact Theory as a Framework for Experiential Activities as Diversity Education: An Exploratory Study

Abstract: Participation in experiential education is said to enhance people's appreciation for diversity. In this study, a pre-test/post-test design found significant changes in participants' attitudes, beliefs, and behaviors following a nonformal diversity education program using adventure-based and community service activities. Additionally, hypothesized program conditions, as outlined by contact theory, were significantly predictive of outcomes, although majority and minority participants differed on their perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Phillips and Lowery (2015) found that when people are provided evidence of their privilege, they often focus upon their personal life hardships to try to facilitate equalizing status beliefs. This is consistent with Seaman et al (2009) who hypothesized from their study of a racially diverse group of students involved in an adventure-based team building and community service activity that minority group members were more likely to perceive social status differences. This is an interesting line of research that could be especially important if status equality beliefs have the effect of hiding or ignoring the marginalization of other group members.…”
Section: Status As Equalsupporting
confidence: 86%
See 4 more Smart Citations
“…Phillips and Lowery (2015) found that when people are provided evidence of their privilege, they often focus upon their personal life hardships to try to facilitate equalizing status beliefs. This is consistent with Seaman et al (2009) who hypothesized from their study of a racially diverse group of students involved in an adventure-based team building and community service activity that minority group members were more likely to perceive social status differences. This is an interesting line of research that could be especially important if status equality beliefs have the effect of hiding or ignoring the marginalization of other group members.…”
Section: Status As Equalsupporting
confidence: 86%
“…Similarly, OOPs, instead of directly focusing on orientation to college, set the conditions for interpersonal interaction by focusing upon group living. Seaman et al (2009) explain that contact theory "fits well" in the conception of OA programs that provide cooperative activities designed to influence interpersonal relationships (see also Wright & Tolan, 2009). Contact theory may provide a theoretical grounding for outdoor orientation outcomes and if so, it is important to explore the contact condition of equality of social status, particularly as outdoor programs seek to increase enrollment of diverse participants.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations